2010
DOI: 10.1253/circj.cj-09-0248
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis-Based Differences in Response of Global Ventricular Performance to Modified Ultrafiltration in Children

Abstract: Background: To determine diagnosis-based differences in the response of global ventricular performance to modified ultrafiltration (MUF) using transesophageal echocardiography during congenital heart surgery. Methods and Results:The study included 38 children with atrial septal defect (n=10), ventricular septal defect (VSD) (n=8), tetralogy of Fallot (TOF) (n=9), or a single ventricle (n=11). Arteriovenous MUF was performed for 10-15 min after cardiopulmonary bypass (CPB). The myocardial performance index (MPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…13 The pump priming solution consisted of sufficient crystalloid and 20% albumin to keep the hematocrit value between 25% and 30%. Anticoagulation was accomplished by intravenous administration of heparin sulfate, which was neutralized with protamine sulfate at the end of CPB.…”
Section: Anesthetic Technique and Cardiopulmonary Bypass (Cpb)mentioning
confidence: 99%
“…13 The pump priming solution consisted of sufficient crystalloid and 20% albumin to keep the hematocrit value between 25% and 30%. Anticoagulation was accomplished by intravenous administration of heparin sulfate, which was neutralized with protamine sulfate at the end of CPB.…”
Section: Anesthetic Technique and Cardiopulmonary Bypass (Cpb)mentioning
confidence: 99%
“…22 They found improved global ventricular function as measured by myocardial performance index as well as fractional shortening with MUF. 22 Interestingly, the magnitude of benefit was negatively correlated with length of CPB and aortic cross-clamp time. 22 Overall, this study, in addition to the study by Chaturvedi et al, showed no change in any diastolic function parameter which adds to the polarity in the literature as Davies et al found improved diastolic performance.…”
Section: Myocardial Functionmentioning
confidence: 95%
“…There is a substantial body of evidence that MUF can hemoconcentrate to this effect. 1,[14][15][16][17][18][19][20][21][22][23][24] Furthermore, there is evidence that higher flow or longer duration of MUF significantly improves the hemoconcentration capabilities. 25,26 Red blood cells (RBCs), platelets, prothrombin (70 kDa), fibrinogen (340 kDa), and albumin (65 kDa) are larger than common ultrafiltrator membrane pore sizes of 60 to 65 kDa and have been shown to be concentrated by MUF; however, smaller coagulation factors such as factor IX (55 kDa) and X (38 kDa) were not.…”
Section: Coagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…MUF was introduced in 1991 and is the process of ultrafiltration immediately following the completion of CPB [2]. In children, MUF has been shown to have clinical benefit by decreasing total body water, improving myocardial contraction, decreasing transfusion requirements and intensive care unit lengths of stay [2,4,5]. The most accepted beliefs for the clinical improvement are the removal of excess free water and its subsequent hemoconcentation effects [2,4].…”
Section: Introductionmentioning
confidence: 99%